Nitration of succinyl-CoA:3-oxoacid CoA-transferase in rats after endotoxin administration - Marcondes, Sisi (The National Academy of Sciences, 2001)
The tyrosine nitration of proteins has been observed in diverse inflammatory conditions and has been linked to the presence of reactive nitrogen species. From many in vitro experiments, it is apparent that tyrosine nitration may alter the function of proteins. A limited number of experiments under in vivo conditions also demonstrate that protein nitration is associated with altered cellular processes. To understand the association of protein nitration with the pathogenic mechanism of the disease, it is essential to identify specific protein targets of nitration with in vivo or intact tissue models. Using anti-nitrotyrosine antibodies, we demonstrated the accumulation of nitrotyrosine in a 52-kDa protein in rat kidney after lipopolysaccharide treatment. The 52-kDa protein was purified and identified with partial sequence as succinyl-CoA:3-oxoacid CoA-transferase (SCOT; EC 2.8.3.5). Western blot analysis revealed that the nitration of this mitochondrial enzyme increased in the kidneys and hearts of lipopolysaccharide-treated rats, whereas its catalytic activity decreased. These data suggest that tyrosine nitration may be a mechanism for the inhibition of SCOT activity in inflammatory conditions. SCOT is a key enzyme for ketone body utilization. Thus, tyrosine nitration of the enzyme with sepsis or inflammation may explain the altered metabolism of ketone bodies present in these disorders.